2015
DOI: 10.3390/nano5020614
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Structural Properties of Si Nanocrystals in SiO2 Films

Abstract: Optical and structural properties of Si nanocrystals (Si-nc) in silica films are described. For the SiOx (x < 2) films annealed above 1000 °C, the Raman signal of Si-nc and the absorption coefficient are proportional to the amount of elemental Si detected by X-ray photoelectron spectroscopy. A good agreement is found between the measured refractive index and the value estimated by using the effective-medium approximation. The extinction coefficient of elemental Si is found to be between the values of crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 158 publications
(372 reference statements)
2
25
0
Order By: Relevance
“…This further supports the interpretation that LW phonons originate from surface/interface of smaller Si NCs, whereas, HW phonons originate from core of larger Si NCs. Similar experimental observations have been reported by Nikitin et al They observed that the wavenumbers in the Raman spectra of smaller (10–20 Å) and larger (>40 Å) Si NCs lie in the ranges 490–500 and 518–519 cm −1 , respectively, which further supports our interpretation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This further supports the interpretation that LW phonons originate from surface/interface of smaller Si NCs, whereas, HW phonons originate from core of larger Si NCs. Similar experimental observations have been reported by Nikitin et al They observed that the wavenumbers in the Raman spectra of smaller (10–20 Å) and larger (>40 Å) Si NCs lie in the ranges 490–500 and 518–519 cm −1 , respectively, which further supports our interpretation.…”
Section: Discussionsupporting
confidence: 93%
“…We wish to emphasize that the results obtained from theoretical calculations of Raman spectra clearly elucidate dominant contribution of Si atoms located at the surface. This further [67] They observed that the wavenumbers in the Raman spectra of smaller (10-20 Å) and larger (>40 Å) Si NCs lie in the ranges 490-500 and 518-519 cm À1 , respectively, which further supports our interpretation. On the other hand, the calculated wavenumber of a strong peak in the Raman spectra of hydrogen terminated cluster is much lower (~499 cm À1 ) than the corresponding wavenumber in oxygen terminated cluster.…”
Section: Calculation Of Raman Spectra Of Si Cluster (Si 41 ) With Difsupporting
confidence: 88%
“…An ensemble of nanostructured silicon particles embedded into an SiO 2 host has been the subject of intensive research over the last two decades. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The main motivation for research in this eld is the fabrication of silicon-based light emitters, which utilize the reduced dimension connement effect to overcome indirect bandgap limitations for radiative recombination in Si. 2,11,12,15 It is also worth citing some other applications of Si nanoparticles, such as photovoltaic cells, 14,21,22 batteries, 23,24 etc.…”
Section: Introductionmentioning
confidence: 99%
“…The position and the width of the Raman band of Si-nc provide a valuable information on their sizes, stress, and temperature13141516. A known problem of conventional Raman spectroscopy is a small cross-section of this process.…”
mentioning
confidence: 99%